Napoleoni sõdade kaja Eesti kunstikogudes [Echoes of Napoleonic Wars in Estonian Art Collections] - Kreem, Tiina-Mall (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2013)
Artistic images of Napoleon Bonaparte, his victories and defeats have had an instrumental role in the modern and historical reception of the Frenchman who endeavoured towards world domination. Pieces on Napoleonic subjects in Estonian art collections not only speak of the locals’ personal interest towards him but also reveal the interconnectedness of the regional historical consciousness and European art created for the purposes of propaganda.(Longer version of the current abstract is included in the article, starting from p 129.)